2020
DOI: 10.17478/jegys.658401
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing EFL students’ writing skills on English through Facebook and classroom collaborative activities

Abstract: The aim of research was to find out the use of Facebook and classroom collaborative activities on students' writing skill of Indonesian Senior High School Students. The researchers used quantitative method by applying quasi-experimental design. The study consisted of 40 students as respondents that were divided into control and experimental group. This is to see which group is effective to be used in helping the students' writing ability. The first group was taught by using Facebook and the second group was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In other words, Facebook is really creative and innovative for writing classroom. It is supported by some previous researchers who investigated the same media, for instance, Putri (2018), Friatin (2018), andSyafrizal et al (2020). They found that the implementation of Facebook in English writing classroom improves the students' discussion and participation in teaching-learning activities.…”
Section: Facebooksupporting
confidence: 52%
See 2 more Smart Citations
“…In other words, Facebook is really creative and innovative for writing classroom. It is supported by some previous researchers who investigated the same media, for instance, Putri (2018), Friatin (2018), andSyafrizal et al (2020). They found that the implementation of Facebook in English writing classroom improves the students' discussion and participation in teaching-learning activities.…”
Section: Facebooksupporting
confidence: 52%
“…Furthermore, it has some advantages for teaching and learning process. As stated by Syafrizal et al, (2020) there are many benefits from implementing Facebook, group discussion between teacher and students, for instance, asking the students to send their assignment or reminding the students about their tests and quizzes. It is in line with Putri (2018) who revealed that the teachers can deliver more material using this media since the teaching and learning process can be done outside the classroom so the teachers do not take much time in explaining the materials.…”
Section: Facebookmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of media can be a valuable tool for teachers to inspire and motivate students in their quest for mastery of the English language. Media serves as a conduit for communication, particularly in educational settings where it provides content to students to enhance effective instruction (Syafrizal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, educators must adopt innovative teaching materials and methodologies that resonate with students and teachers. Integrating various media into the learning environment has been recommended to make lessons more engaging and relevant (Syafrizal et al, 2020). Comprehensive language education should encompass practical communication scenarios such as introductions, telephone conversations, requests, interruptions, expressions of gratitude, apologies, and social greetings.…”
Section: Introductionmentioning
confidence: 99%